2019
DOI: 10.3389/fonc.2019.00567
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Potentially Facilitates the Occurrence of Radiation Encephalopathy in Patients With Nasopharyngeal Carcinoma Following Radiotherapy: A Multiparametric Magnetic Resonance Imaging Study

Abstract: Radiation encephalopathy (RE) is deemed to be a disease induced only by radiotherapy (RT), with the effects of chemotherapeutic agents on the brains of nasopharyngeal carcinoma (NPC) patients being largely overlooked. In this study, we investigated structural and functional brain alterations in NPC patients following RT with or without chemotherapy. Fifty-six pre-RT, 37 post-RT, and 108 post-CCRT (concomitant chemo-radiotherapy) NPC patients were enrolled in this study. A surface-based local gyrification index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Although volume-based functional metrics have been commonly adopted to investigate functional alterations in a variety of diseases, they neglect the intersubject variability in cortical folding patterns (Li et al, 2014 ). In contrast, in the surface-based space, anatomical regions can be accurately matched with the same locations in the standard template, which decreases intersubject variability and increases statistical power (Fischl et al, 1999 ; Argall et al, 2006 ; Li et al, 2014 ; Zhang Y. et al, 2019 ). Therefore, compared with volume-based functional metrics, surface-based ones are more specific to the intrinsic functional organization of the cortical mantle and have moderate to high test–retest reliability (Jiang and Zuo, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although volume-based functional metrics have been commonly adopted to investigate functional alterations in a variety of diseases, they neglect the intersubject variability in cortical folding patterns (Li et al, 2014 ). In contrast, in the surface-based space, anatomical regions can be accurately matched with the same locations in the standard template, which decreases intersubject variability and increases statistical power (Fischl et al, 1999 ; Argall et al, 2006 ; Li et al, 2014 ; Zhang Y. et al, 2019 ). Therefore, compared with volume-based functional metrics, surface-based ones are more specific to the intrinsic functional organization of the cortical mantle and have moderate to high test–retest reliability (Jiang and Zuo, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, compared with volume-based functional metrics, surface-based ones are more specific to the intrinsic functional organization of the cortical mantle and have moderate to high test–retest reliability (Jiang and Zuo, 2016 ). Two recent studies showed that surface-based ReHo, instead of volume-based ReHo, could be a useful index to investigate the pathogenesis of major depressive disorder and bipolar disorder (Li et al, 2014 ; Zhang Y. et al, 2019 ). Similar phenomena could also be observed in the structural domain.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective cross-sectional study included 201 patients with pathologically diagnosed NPC from March 2011 to July 2015. They were divided into three groups according to the difference in treatment methods: the Pre-RT group (56 NPC patients who had not received treatment), the Post-RT group (37 NPC patients who had received RT) and the Post-CCRT group (108 NPC patients who had received CCRT) ( 21 ). To measure the effect of RT or CCRT on the structure of subcortical nuclei, other possible confounding factors (such as age, sex, time intervals between RT and sMRI examinations, RT technology, and maximum RT dosage to the temporal lobes) had to be evenly distributed among the groups.…”
Section: Methodsmentioning
confidence: 99%
“…For each NPC patient, the following clinical data were available: the Karnofsky Performance Status (KPS) score, the main side of NPC, clinical stage, RT techniques, maximum dosage of RT to the temporal lobes, time intervals between RT and MRI examination, detailed information on the chemotherapy agents. All patients receiving RT were given Intensity-modulated radiation therapy (IMRT) or conventional two-dimensional radiotherapy (2D-CRT), as shown in Table 1 [see our previous work ( 21 )]. All patients who presented with stage II-IV NPC according to the 7th edition of the UICC/AJCC (2009) TNM classification (T = Tumor, N = Nodes, and M = Metastasis) ( 23 ) received CCRT, either with or without neoadjuvant/adjuvant chemotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation